34.0k views
5 votes
. Let f(x) = x2 and g(x) = x − 3. Evaluate (g ∘ f)(−2). 1 7 20 −20

2 Answers

2 votes

ANSWER

1

Step-by-step explanation

The given functions are:


f(x) = {x}^(2)

and


g(x) = x - 3


(g \circ \: f)(x) = f(g(x))


(g \circ \: f)(x) = g( {x}^(2) )


(g \circ \: f)(x) = {x}^(2) - 3

We substitute x=-2 to obtain;


(g \circ \: f)( - 2) = {( - 2)}^(2) - 3

We simplify to obtain:


(g \circ \: f)( - 2) = 4- 3


(g \circ \: f)( - 2) = 1

The first choice is correct.

User Bogdacutu
by
5.1k points
1 vote

For this case we have the following functions:


f (x) = x ^ 2\\g (x) = x-3

We must find
(g_ {0} f) (x)

By definition we have to:


(g_ {0} f) (x) = g (f (x))

So:


g (f (x)) = (x ^ 2) -3 = x ^ 2-3

We must evaluate the composite function for
x = -2


g (f (-2)) = (- 2) ^ 2-3 = 4-3 = 1

ANswer:


g (f (-2)) = 1

User Fczbkk
by
5.5k points